FIGURE 2 in The genus Callitriche (Plantaginaceae: Callitricheae) in South America - Lansdown, Richard V.; Hassemer, Gustavo (Zenodo, 2021)
FIGURE 2. Lectotype of Callitriche antarctica (J.D. Hooker s.n., MEL barcode MEL2409648). Copyright: Royal Botanic Gardens Victoria. Published as part of Lansdown, Richard V. & Hassemer, Gustavo, 2021, The genus Callitriche (Plantaginaceae: Callitricheae) in South America, pp. 85-118 in Phytotaxa 501 (1) on page 89, DOI:10.11646/phytotaxa.501.1.3, http://zenodo.org/record/5424744